2004
DOI: 10.1002/bdrb.20011
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal closure of membranous ventricular septal defects in Sprague‐Dawley rat pups after maternal exposure with trimethadione

Abstract: Treatment-induced VSD close postnatally, and appears to be a delay in cardiac development not associated with fetal weight. The timing of closure and survivability during closure is dependent on the severity of the VSD. Further characterization of the two sizes of VSD may provide diagnostic clarity; however, the current data support the smaller VSD as a variation with no significant impact on viability and growth, and the more severe VSD to be a malformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 11 publications
3
39
2
Order By: Relevance
“…Although 70% of small VSDs in human infants usually resolve on their own during the first 2 years of life, large VSDs are known to cause failure to thrive, especially if compounded by other anomalies (Turner et al, 2002;Rudolph, 2009). Similarly, in rodents, small VSDs can resolve whereas the closure of larger VSDs may be less common (Fleeman et al, 2004). It would be of interest to conduct a study in our mouse model postnatally to determine whether the VSD or the thinner ventricular walls are present at birth or whether they can resolve prenatally or in the early postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Although 70% of small VSDs in human infants usually resolve on their own during the first 2 years of life, large VSDs are known to cause failure to thrive, especially if compounded by other anomalies (Turner et al, 2002;Rudolph, 2009). Similarly, in rodents, small VSDs can resolve whereas the closure of larger VSDs may be less common (Fleeman et al, 2004). It would be of interest to conduct a study in our mouse model postnatally to determine whether the VSD or the thinner ventricular walls are present at birth or whether they can resolve prenatally or in the early postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…6). The mean incidence of VSD in control was 14 AE 25% and entirely attributable to one litter with a 44% incidence of VSD (normal background rates are 2-3%; Fleeman et al, 2004;Solomon et al, 1997). No DMO was detected in the serum of this dam, ruling out the possibility that these spurious findings were the result of dosing error and therefore there was no rationale for excluding this dam from study.…”
Section: The Effect Of Dmo On Malformationsmentioning
confidence: 94%
“…However, more recent studies reported dose-limiting maternal toxicity above 300 mg/kg b.i.d. and only a 50% incidence of VSD (Fleeman et al, 2004). We believe the heightened maternal sensitivity to TMD was the result of the re-derivation of the Sprague-Dawley rat by Charles River in 1998 to yield the Crl:CD(SD)IGS BR foundation colony (White and Lee, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been proved that small VSDs induced by prenatal exposure to trimethadione did not significantly affect fetal viability or growth (7). Unlike all other COX inhibitor studies, the developmental effect was treatment-related.…”
Section: Discussionmentioning
confidence: 94%